Axial compressive behavior of polyethylene terephthalate/carbon FRP-confined seawater sea-sand concrete in circular columns. (20th February 2020) - Zeng, Jun-Jie; Gao, Wan-Yang; Duan, Zhi-Jian; Bai, Yu-Lei; Guo, Yong-Chang; Ouyang, Li-Jun
Highlights: Axial compressive behavior of PET FRP/CFRP-confined SSC columns was investigated. The type and thickness of FRP jackets and the type of mixing water of SSC were the variables of this study. A modified analysis-oriented model with a new dilation equation was proposed for the PET FRP-confined SSC. Abstract: Since fiber-reinforced polymer (FRP) composites possess excellent corrosion resistance, they have great potential of use with seawater sea-sand concrete (SSC) for the construction of marine and coastal infrastructure. The existing research on SSC columns confined with FRP jackets, however, is rather limited. Most of the limited research has focused on the axial compressive behavior of SSC columns confined by conventional FRP jackets (made from carbon and glass FRP composites). This paper presents results from the first-ever experimental study on the behavior of axially loaded circular SSC columns confined by polyethylene terephthalate (PET) FRP jackets, which are composed of a new and more promising type of FRP composites with a bilinear stress-strain response and a large rupture strain. Parameters varied between the tests presented in this paper included the type and thickness of FRP jackets and the type of mixing water used for casting the SSC. A modified analysis-oriented model was developed in which a new dilation equation was proposed for the PET FRP-confined SSC. The reliability and accuracy of the analysis-oriented model were then examined by comparisons between the predicted results and the test results of the FRP-confined SSC.